Internetworking with TCP/IP Vol-III: client-server programming and applications - Comer, Douglas; Stevens, David (New Delhi : Prentice Hall of India, 2004)
Computer Science
Keywords: Internetworking; Software design; Client server software; Program interface; Socket interface; Client software; Multiprotocol servers; Multiservice servers; Telnet client; Systen protocol